A Promessa de Efetividade das Medidas Executivas Atípicas na Execução Trabalhista: uma análise translacional das execuções do Tribunal Regional do Trabalho da 9a Região de 2018 a 2020 - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
The fundamental right to non-defeasibility of jurisdiction, contained in article 5, XXXV, of the Constitution of the Federal Republic of Brazil, must be interpreted as the right to effective judicial protection, meaning the factual realization of substantive law. Among the procedural techniques provided by the 2015 Code of Civil Procedure, through article 139, IV, the use of inductive, coercive, mandatory and sub rogatory measures – already contained in the previous Code concerning obligations to do, to not doing and delivering things – was extended to ensure compliance with court orders regarding pecuniary obligations. The legal novelty was received with restrictions by doctrine and jurisprudence, which limited its scope. In 2023, the Federal Supreme Court, in Direct Action of Unconstitutionality n. 5,941, recognized its constitutionality and ratified the possibility of adopting atypical provisional measures, as long as the principles of due process of law, proportionality and reasonableness are observed. Therefore, the scope of the work is to confirm or refute the hypothesis raised by the doctrine that the application of atypical provisional measures really contributes to the effectiveness of execution in the Labour Process. To this end, using the inductive method, quantitative and qualitative analyses were made of 461 (four hundred and sixty-one) lawsuits in progress before the Regional Labour Court of the 9th Region (State of Paraná, Brazil) in which one or more atypical provisional measures were granted and implemented between 2018 and 2020. The analysed measures were mainly the seizure of national driver's licenses and passports and the blocking of credit cards. It was considered that the measures contributed to the effectiveness of the execution when the executed party expressly requested the lifting of the restrictions and/or when the debt was paid within 2 (two) years after its implementation. An effectiveness rate of 21.48% (twenty-one and forty-eight hundredths of a percent) was reached when the atypical provisional measures were considered jointly. The most effective measures were the seizure of the debtors’ passports and driver's licenses, with effectiveness rates of 45.45% (forty-five and forty-five hundredths of a percent) and 29.8% (twenty-nine and eight tenths of a percent) respectively. Given the great contribution of atypical provisional measures to the effectiveness of labour execution, confirming the initial hypothesis, adopting the jurimetric and translational methodological perspectives, a review of the theory was suggested regarding the subsidiarity of their application, defending that it should be done immediately, in case of silence of the executed party after the summons for payment or in case of absence of a cooperative attitude. Analysing effectiveness from endo- and pan-procedural perspectives, the burden of time in execution should not be borne by the creditor or the Judiciary; it is the executed party who should fully demonstrate that the execution can be carried out in a less burdensome way.
Keywords: tutela jurisdicional efetiva; medidas executivas atípicas; execução trabalhista; jurimetria; metodologia translacional; effective judicial protection; atypical provisional measures; labour execution; jurimetrics; translational methodology; CNPQ::CIENCIAS SOCIAIS APLICADAS::DIREITO